Determining teachers’ behaviors concerning the NCTM standards in low and high performing rural high schools in Kansas - Young, Lanee (Kansas State University, 2007)
This study was designed to investigate teaching practices of mathematics teachers in rural high schools in Kansas in the context of the NCTM Principles and Standards. National reports advocate for change in the mathematics classroom while state assessments force teachers to focus on test scores. This study investigated the extent to which teachers whose students experienced repeated success on state assessments integrated the NCTM Process and Content Standards into the mathematics classroom. Those data were then compared with the teaching practices in schools whose students repeatedly did poorly on state assessments. This two-phase study used both quantitative and qualitative data from four main sources: survey, interview, observation, and collection of artifacts. Phase I surveyed all mathematics teachers in high performing and low performing rural high schools throughout the state of Kansas. Data collected in Phase I were used to examine differences and similarities in teaching practices of teachers from high and low performing schools. During Phase II qualitative data were collected and analyzed to further explore any existing patterns among high performing and low performing schools. Results from teachers in high and low performing schools were compared and contrasted to determine if there were differences between the teaching practices that were demonstrated by each group of teachers. Results of surveys, interviews, observations, and artifacts revealed teachers in high performing schools used a variety of different representations to teach and assess a topic while those teachers from low performing schools used one or two representations. Students from high performing schools had more frequent opportunities to communicate with the teacher to gain additional assistance in learning the mathematics content. Teachers in high performing schools also used formal assessment strategies as part of the learning process more consistently than their counterparts from low performing schools. Results from interviews, observations, and artifacts reveal that teachers in high and low performing schools implement teaching practices aligned with the algebra content standards in a very similar manner.
Keywords: NCTM Standards; Math Education; Rural Schools; Teaching Practices; Education, Mathematics (0280); Education, Secondary (0533)